Preprocedural ultrasound as an adjunct to blind conventional technique for epidural neuraxial blockade in patients undergoing hip or knee joint replacement surgery: A randomised controlled trial - Kompal Jain (Indian Journal of Anaesthesia, 2019)
Background and Aims: The patients undergoing total knee and hip replacement surgeries are mostly obese, more than 50 years of age with osteophytic spine and spine deformities making the blind conventional technique of regional anaesthesia more difficult. The aim of the study was to compare the role of preprocedural ultrasound scan to conventional blind technique in obese patients with osteophytic spines undergoing total knee or hip replacement surgeries in terms of technical difficulty, clinical efficacy, safety and patient comfort. Methods: A prospective, randomised controlled trial was conducted in which 210 consenting American Society of Anesthesiologists (ASA) grade III patients, age >50 years, Body Mass Index (BMI) ≥30 kg/m2 with osteophytic spines including abnormalities undergoing joint replacement surgeries were randomised in two groups. Ultrasound group (“B”) received Combined Spinal Epidural Anaesthesia (CSEA) after preprocedural lumbar ultrasound scan. In control group (“A”), CSEA was given by blind conventional technique. The primary objective was to compare the rate of successful epidural block on 1st needle insertion attempts in both the groups. The secondary objectives were to compare both groups in terms of ease, success, comfort and safety of epidural block. Results: Ultrasound improved success of CSEA at 1st attempt from 74.3% in control group (“A”) to 85.7% in Ultrasound group (“B”) (P = 0.038). Fewer needle insertion attempts, passes and anaesthesiologist were required in ultrasound group. Pearson correlation coefficient was 0.976 using both views. Conclusion: Preprocedural ultrasound scan is a useful adjunct to lumbar epidural blocks in obese patients with osteophytic abnormal spines.